Mediation Model Investment Opportunity Set on Manufacturing Companies in Indonesia: Partial Least Square (PLS) Approach - Khoirul Hikmah; Agung Satmoko; Rifqi Syarif Nasrulloh (Journal of Business Innovation and Research, 2022)
The purpose of the study was to test and analyze the influence of multinationality, size, and profitability as company advantages, and leverage and systematic risk as company limitations on the change in investment opportunity set with its appropriate proxy and influence on company financing. The sample of the study are manufacture firms listed on the Indonesian Stock Exchange that distributed successively in 2010 – 2013. Sample size consists of total is 435 firms Data analysis was conducted in two ways: a) Confirmatory Factor Analysis (CFA) to find appropriate proxies; and b) Partially Least Square (PLS). Results: company advantages were proven to have a positive effect on Investment Opportunity Set (IOS). Company limitations were not proven to have a negative effect on Investment Opportunity Set (IOS). Investment Opportunity Set was proven to have a positive effect on corporate financing policies at 10% significance level. Company advantages were proven to have a negative effect on corporate financing policies. Company limitations were proven to have a negative effect on corporate financing policies. IOS was proven to mediate the influence of company advantages on corporate financing policies at 10% significance level. IOS was proven to mediate the influence of company limitations on corporate financing policies. Company limitations have no significant influence on investment opportunity set. This is because companies inIndonesia have yet considered the leverage and systematic risk in determining the directions of corporate investment policies to grow and develop as well as in determining their financing policies.